Molecular Genotyping of Tsst-1 Gene Staphylococcus Aureus from Clinical Specimen - Puspitarini, Marinda Dwi; Setyarini, Wahyu; Hadi, Usman; Kuntaman, Kuntaman (Folia Medica Indonesiana, 2021)
Staphylococcus aureus (S. aureus) is the most common pathogen in humans that causes various infections. Variations in infections due to S. aureus are related to the presence of virulence factors, one of which is Toxic Shock Syndrome Toxin-1 (TSST-1) which is the main cause of Toxic Shock Syndrome (TSS). This study aimed to explore the genetic pattern of the tsst-1 genes among MSSA and MRSA from clinical isolates of patients at Dr. Soetomo Academic Hospital, Surabaya-Indonesia. PCR examination was performed on 106 clinical samples of S. aureus isolates to determine the presence of the tsst-1 genes; subsequently, phylogenetic analysis was performed. The positive tsst-1 genes were found in 3 (5.7%) MSSA isolates and 2 (3.8%) MRSA isolates from 106 samples, of which were divided into 53 MSSA isolates and 53 MRSA isolates. No significant difference was noticed between the tsst-1 genes on both the MSSA and MRSA bacteria (p = 0.648). The positive tsst-1 genes were found in 1 (4.5%) of pus specimens and 2 (16.7%) of blood specimens from MSSA isolates. However, the positive tsst-1 genes were found in neither sputum nor urine specimens. The genes were found in 2 (16.7%) of blood specimens from MRSA isolates. Based on the phylogenetic tree, Indonesian tsst-1 isolates belonged to the same clade as Japan, Iran, Iraq, India, Egypt and the United Kingdom isolates. The prevalence of tsst-1 genes of both MSSA and MRSA from clinical isolates in Dr. Soetomo Academic Hospital Surabaya are 5.7% and 3.8%, respectively. The tsst-1 genes of Surabaya-Indonesia, Japan, Iran, Iraq, India, Egypt and the United Kingdom belonged to the same clade.